Mobile phone marketing - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
There is ever-increasing competition in the international mobile phone market. Therefore, in order to be successful, mobile phone companies must come up with creative new marketing and advertising campaigns. This case study follows one such success story, in the form of the Nokia N8 campaign in the Philippines.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Mobile Phone Marketing. In International marketing (p. 479). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Advertising -- Cell phones -- Case studies; Export marketing -- Case studies